GRAFIK PENGENDALI RAGAM SAMPEL UNTUK MONITORING VARIABILITAS PROSES PRODUKSI - Sudarno, Sudarno (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
The control chart is a graphical display or a quality characteristic that has been measured or computed from a sample versus the sample number or time. The variance chart is used to monitoring variability of production process. It is an altenative way to check variability process rather than R chart or s chart. The problems will be done are find the parameters of variance chart, predict process capability, verify defect per million opportunities (DPMO) of process result and simulation kinds of shift sigma values. This result could be used as information to production process at the future time. The result of discussion that upper conrol limit = 0.0014, center line = 0.00073, lower control limit = 0.00028, process capability = 1.003 and DPMO = 2,620 part per million. These parameters used for information in the next production process. Keywords: Variance Chart, Process Capability, Defect per million opportunities, Shift.